2016
DOI: 10.1039/c5ra21617f
|View full text |Cite
|
Sign up to set email alerts
|

Remote triggering of thermoresponsive PNIPAM by iron oxide nanoparticles

Abstract: Thermoresponsive PNIPAN can be remotely triggered by embedded iron oxide nanoparticles under an AC field, and the transition temperature can be tuned by changing the ionic concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…When the SAR is plotted against H 2 the result is indeed a linear relation, as shown in Figure 5(b) . It was previously reported that when IOMNPs are dispersed by themselves in DIW, with no PNIPAM present, at a concentration of 1 mg mL −1 the SAR was approximately 220 W g −1 (Denmark et al., 2016 ). That data corresponded to a field strength of 59.1 kA m −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the SAR is plotted against H 2 the result is indeed a linear relation, as shown in Figure 5(b) . It was previously reported that when IOMNPs are dispersed by themselves in DIW, with no PNIPAM present, at a concentration of 1 mg mL −1 the SAR was approximately 220 W g −1 (Denmark et al., 2016 ). That data corresponded to a field strength of 59.1 kA m −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The IOMNPs used in this work were characterized previously (Denmark et al., 2016 ). Briefly, their discreet size was measured by transmission electron microscopy (TEM) and found to be approximately 10 nm in diameter on average.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced changes in the NC can range from alterations in porosity to the cleavage of molecular linkers to activate a specific functionality. Techniques like these have been shown to significantly enhance the therapeutic efficiency of in vivo administration by avoiding potentially toxic non-specific interactions or premature drug release, while also ensuring that an adequate concentration of drug is delivered to the target site (18,(20)(21)(22)(23).…”
Section: Nanotherapies: State Of the Artmentioning
confidence: 99%
“…Biomedical research has benefited the most and progressed the furthest through nanotechnology. For example, magnetic nanoparticles are applied to targeted and triggered drug delivery (76)(77)(78), gold nanoparticles bind antibodies in conventional biosensing (79)(80)(81), and zinc oxide and titanium dioxide nanoparticles protect skin (82,83). Solutions to the challenges MIPs originally presented have been found through MIP nanoformulations or by incorporating them with nanomaterials (46, 84,85).…”
Section: Introductionmentioning
confidence: 99%